Umur Dan Paritas Dengan Kejadian Abortus Di RSIA Citra Keluarga Kota Kediri - Dwi Ertiana; Taurisiawati Rahayu , Dewi; Ferliya Angreini, Dian (STIKES dan AKZI Karya Husada Kediri, 2024)
Abortion is one of the causes of maternal morbidity and mortality associated with pregnancy at an early age. The incidence of spontaneous abortion in Indonesia based on age group is 3.8%. According to WHO, the percentage of abortions is quite high, around 15 - 40%. The Incidence rate is known in mothers who have been declared positive for pregnancy and 60 - 75% of abortions occur before 12 weeks of gestation. This research aims to find out whether there is a relationship between age and parity and the incidence of abortion. Retrospective analytical research method using data from medical records. The research was carried out from 25 to 31 August 2023 at Rsia Citra Keluarga Kediri City, with a total sampling technique of 77 respondents, the research instrument used a questionnaire, and data analysis used the chi-square test. The results of the research were that 9.0% of the age group were at risk and experienced abortion, and 28.6% were multiparous and experienced abortion. The statistical test obtained (p-value) = 0.003 (< ɑ = 0.05) which means there is a significant relationship between maternal age and the incidence of abortion. The results of the chi-square statistical test to determine the relationship between parity and the incidence of abortion were obtained (p-value) = 0.043 (< ɑ = 0.05) which means there is a significant relationship between maternal parity and the incidence of abortion. Maternal age < 20 years indicates a physical and psychological condition that is not yet ready, age > 35 years indicates a sign that reproductive organs are not working optimally such as those of productive age, high parity indicates how the condition of the uterine muscles is getting weaker and unable to maintain pregnancy, so women need to give education before planning a pregnancy, during pregnancy, and spacing of pregnancies so that women are better prepared and able to maintain their pregnancies to avoid abortion.